The Effectiveness of Atlas Media Based On Constructivist Approach in College to Improving Learning Outcome in Plant Anatomy - M Mulyati; Lince Meriko (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
This study aims to determine the effectiveness of Altas media based on constructivist approach towards improving student learning outcomes in Plant Anatomy. This study used a pretest and posttest pre-experimental design. Data were analyzed descriptively and statistically, namely analyzing observations of the ability of lecturers to manage learning, student activities during learning using atlas media based on constructivist approach abilities before and after using atlas media. The results showed that the atlas media was effectively used in learning with the ability of lecturers to manage 80.5 learning included in the excellent category and during collage activities 80.3 students studied included in the very active category. These results indicate that learning using atlas media is more effective in improving learning outcomes in plant anatomy